Lexical blends and neologisms: some concepts and problematizations - Prearo-Lima, Rafael [UNESP] (Federal Univ Ceara, 2019)
The process of neology formation shows how dynamic languages are: as society changes, new words are necessary to describe these changes. Having that in mind, the goal of this paper is to observe the formation of neologisms based on a process of word formation known as lexical blends. To do so, firstly we will present and discuss some concepts in the lexicological field regarding neologisms and how to identify them. After that, we will present the concept of lexical blends and how these are formed. Then, we will analyze occurrences of lexical blends between the word crente (believer, namely, those of Christian faith) and other words, discussing whether these occurrences may be considered as neologisms. Such blends have been collected from the social media Twitter and selected as their meaning could be evident based on their use. For our theoretical basis, we will use the definitions of neologisms based on Rey (1976), Alves (1996, 2001, 2007), Rio-Torto (2007) and Cano (2007), besides considering the studies of Goncalves (2003, 2006, 2012) regarding lexical blends. Based on the current definition of neologisms, the analysis indicates it is difficult to determine lexical blends as a neologism, indicating the need to deepen the theoretical discussion to set clearer boundaries regarding the identification of such phenomenon.
Keywords: Lexicology; Lexical blend; Neologism